2020
DOI: 10.1038/s42003-020-01166-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of microbial communities across surface waters of the Great Barrier Reef

Abstract: Microorganisms are fundamental drivers of biogeochemical cycling, though their contribution to coral reef ecosystem functioning is poorly understood. Here, we infer predictors of bacterioplankton community dynamics across surface-waters of the Great Barrier Reef (GBR) through a meta-analysis, combining microbial with environmental data from the eReefs platform. Nutrient dynamics and temperature explained 41.4% of inter-seasonal and crossshelf variation in bacterial assemblages. Bacterial families OCS155, Cryom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 76 publications
3
40
0
1
Order By: Relevance
“…Opportunistic copiotrophic taxa, such as Cryomorphaceae , Flavobacteriaceae and Rhodobacteraceae, are usually more prevalent in the higher nutrient nearshore waters (e.g., [ 36 , 37 ]). Recent studies have pinpointed Flavobacteriaceae -affiliated taxa as indicators for increased organic nutrients at the Great Barrier Reef [ 19 , 38 ]. We found that the relative abundances of Cryomorphaceae PS008 were significantly correlated with TOC concentrations in the water (R 2 = 0.77, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Opportunistic copiotrophic taxa, such as Cryomorphaceae , Flavobacteriaceae and Rhodobacteraceae, are usually more prevalent in the higher nutrient nearshore waters (e.g., [ 36 , 37 ]). Recent studies have pinpointed Flavobacteriaceae -affiliated taxa as indicators for increased organic nutrients at the Great Barrier Reef [ 19 , 38 ]. We found that the relative abundances of Cryomorphaceae PS008 were significantly correlated with TOC concentrations in the water (R 2 = 0.77, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[40,41]). Recent studies have found Flavobacteriaceae-affiliated taxa as indicators for increased organic nutrients at the Great Barrier Reef [15,22]. We found that relative abundances of Cryomorphaceae PS008 were significantly correlated with TOC concentrations in the water column (R2 = 0.77, p < 0.001).…”
Section: Discussionmentioning
confidence: 48%
“…Interactions of corals with microorganisms from the surrounding water (coral ecosphere) facilitate the transfer of coral metabolites into the marine microbial food web, thus providing a linkage between corals and the water column that has a strong impact on reef biogeochemical cycling [19]. Due to their sensitivity towards changes in environmental parameters, microbial community data of the coral ecosphere can provide accurate predictions of the environmental status and inform on pivotal tipping-points in reef condition [15,[20][21][22]. Therefore, microbial surveys of the near-coral seawater environment, where microbial interactions between corals and microorganisms occur, have shown to benefit and support long-term coral reef monitoring initiatives [19].…”
Section: Introductionmentioning
confidence: 99%
“…For the same time period, nutrient additions had opposing effects on alpha diversity metrics in biofilms cultured with corals: richness increased with nutrients while evenness decreased. Furthermore, with increased nutrients, populations of bacteria typically associated with oligotrohic coral reefs decreased, including groups of Alphaproteobacteria and Cyanobacteria (e.g., Rhodobacteraceae and Thalassobius, and Rivularia and Synechococcus) 33 , 81 and shifted toward populations of copiotrophic Flavobacteria.…”
Section: Discussionmentioning
confidence: 99%